Analisis Strategi Pemasaran Menggunakan Swot Analysis Pada Cafe Rolet View Jepara - Yoga Prastyo; Bambang Setiyo Pambudi (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The purpose of this research is to determine the business marketing strategy of Rolet View Jepara Cafe through SWOT Analysis. The design used in this research is descriptive qualitative. The sample of this research is managers, employees at Rolet View Jepara Café with a total of five people. The sampling technique used in this research is purposive sampling. The research instrument was conducted by interview, observation and documentation methods. The data analysis used is SWOT Analysis. The results showed the strategies that can be applied are by expanding and maintaining existing markets, increasing marketing through social media by following technological advances, maintaining commitment to the quality of food and beverages as well as conducting socialization to all employees, making improvements and adding to photo spots of natural scenery.